Influence of Work Engagement and Organizational Culture on Employee Performance in Banjarmasin Islamic Hospital - Rahmah, Alpia; Artiningsih, Dwi Wahyu; Wicaksono, Teguh (Journal of Business Management and Economic Development, 2024)
This study intends to build a conceptual model to describe and empirically prove the formation of employee performance through work engagement and organizational culture. This study used quantitative methods and involved 96 non-medical employees as samples. Data were collected using questionnaires, then analyzed by multiple linear regression. Empirically shows that work engagement has a significant effect on employee performance. Employee performance will improve if employees feel valued and obligated to put in full effort at work. Likewise, organizational culture has a significant effect on employee performance. This is because workers who have understood and applied organizational culture effectively to their work activities will force others to follow the rules set by the company, which in turn will encourage improved employee performance. The better the organizational culture, the more employees will care about the company's values and use them as a guide when doing work. With employee engagement and a strong organizational culture will drive performance improvement.